Effects of locus of control on behavioral intention and learning performance of energy knowledge in game-based learning. Issue 6 (3rd July 2017) - Yang, Jie Chi; Lin, Yi Lung; Liu, Yi-Chun
Abstract: Game-based learning has been gradually adopted in energy education as an effective learning tool because digital games have the potential to increase energy literacy and encourage behavior change. However, not every learner can benefit from this support. There is a need to examine how human factors affect learners' reactions to digital games for supporting learning. This study addresses this issue by developing a digital educational game and examining the effects of locus of control on behavioral intention and learning performance of energy knowledge in game-based learning. The results demonstrated that learners with internal locus of control (ILC) outperformed external locus of control (ELC) learners in energy knowledge after interacting with the game. Moreover, the proposed game can reasonably reduce the differences in the behavioral intention of the ILC and ELC learners, indicating that ELC learners significantly improved their behavioral intention after playing the game, especially their external behavioral intention in the aspects of persuasion, legal action, and political action. The findings of this study are discussed to enhance the understanding of locus of control on behavioral intention and energy knowledge in the context of digital games.